Validity and Reliability of Interactive 50-meter Sprint Test for Measuring Horizontal Anaerobic Power of Football College Players - Hamdan, Husham (Journal of Physical Education, 2023)
The research aimed at finding the validity and reliability of 40m sprints test with ball dribble to measure the soccer player’s horizontal ability. The researcher used the descriptive method on (31) college of physical education and sport sciences students who play in Iraqi soccer clubs. Height, weight, and age mediums were (175.52+7.85 cm), (66.26+10.12 kg), and (23.74 + 2.49 years) respectively. 40m sprint test for one time, 40m sprint test with ball dribble for two times with (3) days between each test. The validity and reliability of the test were calculating using criterion validity and discriminant/ divergent validity with 40m sprint test for horizontal ability measuring ability and time. Reliability was calculated using test – retest method, Pearson correlation coefficient and ICC as well as using Bland – Altman Plot. The results showed high levels of reliability and validity. The researcher concluded that 40m sprint test with ball dribbling to measure horizontal ability for soccer players.